Morphological analysis of historical landscapes based on cultural DNA approach - Goodarzi, Parichehr; Ansari, Mojtaba; Mahdavinejad, Mohammadjavad; Russo, Alessio; Haghighatbin, Mahdi; Pour Rahimian, Farzad (Digital Applications in Archaeology and Cultural Heritage, 2023)
Recent trends in landscape architecture investigate new approaches, methods, and technologies to understand, monitor, manage, continuity, and sustainably develop heritage landscapes. Cultural DNA (CD) represents designs' transferable geometric, behavioural and functional properties. The morphological structure of Persian historical gardens possesses discoverable hidden patterns, computable through the CD's mathematical and computational models. This study aims to investigate and discover effective parameters in the spatial structure of historical Persian gardens using Space Syntax. Six Persian Gardens were surveyed, and spatial structures were analysed using DepthMap10 software. The results show that these spaces follow meaningful mathematical patterns and rules that can be formulated in the context of generative processes and generalized for the evolutionary continuity of gardens. However, further research is proposed to develop more advanced computational methods, such as artificial intelligence (AI) algorithms and AI-based decision support tools, to help to generate design scenarios and to transmit culture through the design process. •Historical landscapes follow patterns and specific mathematical rules.•By using a new methodology, we found effective parameters in the spatial layout of historical Persian gardens.•We have collected data of six historical Persian gardens (World Heritage Sites in Iran) using UAVs and have produced detailed plans and a 3D animation video.•The Qajar gardens have higher spatial connectivity than the Safavid garden.•We studied Cultural DNA in Historic Persian Gardens.